San duo tu. ([Tianjin?] : [publisher not identified], 1920)
Coloured poster showing three Blessing Babies (福娃) holding pomegranate, coral and peach symbolising fertility, happiness and longevity respectively.
Keywords: New Year decorations, etc. -- China; Folk art -- China; Posters, Chinese -- 20th century